Robust fuzzy-scheduling control for nonlinear systems subject to actuator saturation via delta operator approach - Yang, Hongjiu; Li, Xuan; Liu, Zhixin; Zhao, Ling (Information sciences, 2014)
This paper focuses on robust fuzzy-scheduling control for nonlinear systems with actuation saturation via delta operator approach. A class of T–S fuzzy delta operator systems is extended to describe nonlinear systems subject to actuator saturation and linear fractional uncertainty. Moreover, a set invariance condition is established for T–S fuzzy delta operator systems. Based on the set invariance condition, an optimization approach is proposed to estimate the domain of attraction for the T–S fuzzy delta operator systems. The domain of attraction is arbitrarily close to a null controllable region by the designed PDC control law or non-PDC control law. Furthermore, the non-PDC control law is proposed by using fuzzy weighting-dependent Lyapunov function. The effectiveness of the developed techniques is shown through a numerical example.